APPOINTMENT OF PROVINCIAL SECRETARIES OF THE HOUSE OF REPRESENTATIVES THROUGH THE APPROVAL OF THE PROVINCIAL COUNCIL REPRESENTATIVES - Toripalu, Huismant Brant (Universitas Tadulako, 2019)
The problem examined is the mechanism for the appointment of secretaries of the Provincial Regional Representative Council with the enactment of Government Regulation Number 18 of 2016 concerning Regional Apparatus and the approval of the leadership of the Provincial House of Representatives in the appointment of secretaries of the Regional People's Representatives Council. The research objective was to find out the mechanism for the appointment of secretaries of the Provincial Regional Representatives with the enactment of Government Regulation No. 18 of 2016 concerning Regional Apparatus and to determine the approval of the leadership of the Provincial House of Representatives in the appointment of secretaries of the Regional People's Representatives Council. The research method uses normative legal research that uses primary legal materials, secondary legal materials, and tertiary legal materials which are then processed and analyzed using interpretation or interpretation techniques and argumentation techniques. The results of the study found that the appointment and dismissal of the Secretary of the Council was not the same as the appointment and dismissal of the State Civil Apparatus, which was generally due to the existence of the position of Secretary of the Provincial House of Representatives as a lex specialist.